Advice taking under uncertainty: The impact of genuine advice versus arbitrary anchors on judgment - Hütter, Mandy; Fiedler, Klaus (Journal of experimental social psychology, 2019)
A major module of rational advice taking consists in the metacognitive ability to distinguish between credible advice and arbitrary anchors. Accordingly, we investigated the extent to which framing the very same information as either advice or anchor exerts a differential influence on quantitative judgments. Four experiments showed that although arbitrary anchors were given lower weight than advice, they nevertheless exerted a systematic impact on final judgments. Degree of integration was related to subjective confidence only in the advice condition, but not in the anchoring condition, suggesting that arbitrary anchors were not considered informative. Framing the source of advice as a human being versus as a computer did not affect our results. Only the aboutness of advice, that is, whether it targeted the focal judgment item, determined its influence on final judgments and on confidence. On the one hand, these findings speak to the (partial) sensitivity of human judges to the source and validity of advice under uncertainty. On the other hand, the persevering effect of arbitrary anchors demonstrates the dependence of judgments on unauthorized influences. Both findings together highlight the need to study advice taking from a metacognitive perspective.
Gesehen am 17.01.2020